ANALISIS KOMPONEN ASAM AMINO IKAN LAYANG DELES (Decapterus Makrosoma) HASIL OLAHAN TRADISIONAL BERDASARKAN LAMA PENYIMPANAN - Vhindra Engson Lumamuly; Nikmans Hattu; Semuel Unwakoly (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2019)
The aim of this study was to determine the amino acid composition of traditional processed Layang Deles fish (Decapterus macrosoma) which was stored for 2 months. Analysis of amino acid content using by Ultra Performance Liquid Chromatography (UPLC) instrument after content of water and lipid in sample was removed. The results of the analysis showed that there was a change in the concentration of 15 amino acids measured ranging from 85.17% to 2,873.42% in acid hydrolysis and 88.18% to 28.73% in alkaline hydrolysis. The biggest changes occurred in histidine, arginine and serine amino acid concentrations of 2,873.42%, 2,606.74% and 900.00% in acid hydrolysis and in amino acids serine, aspartic acid and histidine which were 88.17%, 62, 99% and 40.02% in alkaline hydrolysis. Based on the results of the research, it can be concluded that the processing of inmana fish with a storage period of 2 months affects the amino acid components of Layang Deles fish (Decapterus macrosoma).